Ventral hernia repair with concomitant soft tissue excision improves satisfaction without increased costs - Jacob Christopher Hubbuch; Margaret A Plymale; Daniel L Davenport; Trevor N Farmer; Seth D Walsh-Blackmore; Jordan Hess; Crystal Totten; John Scott Roth (International Journal of Abdominal Wall and Hernia Surgery, 2021)
PURPOSE: Soft tissue management following ventral hernia repair (VHR) may impact wound complications and hernia recurrence. Rationales for soft tissue excision (STE) include ischemia, redundancy, potential space reduction, and cosmesis. This study evaluates outcomes among patients undergoing VHR with and without STE. MATERIALS AND METHODS: Institutional Review Board-approved review of VHR patients at a single institution from 2014 to 2018 was performed for 90-day wound complications, reoperations, and readmissions. Hernia recurrence, chronic pain, functional status, and satisfaction were assessed through telephone survey. Outcomes and costs between groups were analyzed. RESULTS: One hundred and forty-four patients underwent VHR alone; 52 patients underwent VHR/STE. Obesity, larger defects, severe chronic obstructive pulmonary disease, and higher wound classes were more prevalent among VHR/STE. Deep surgical site infection [SSI (1% vs. 8%, P = 0.018)], wound dehiscence (13% vs. 33%, P = 0.003), and return to operating room (1% vs. 12%, P = 0.005) occurred more commonly in VHR/STE. Total costs were more than 50% greater ($18,900 vs. $29,300, P = 0.001) in VHR/STE, but after multivariable analysis adjusting for risk factors, total costs of VHR/STE no longer remained significantly higher ($18,694 vs. $21,370, P = 0.095). Incidence of superficial SSI (6% vs. 6%), seroma formation (14% vs. 12%), non-wound complications (7% vs. 17%), median length of stay (4 vs. 5 days), readmissions (13% vs. 21%), hernia recurrence (38% vs. 13%), and functional status scores (71 vs. 80) did not differ significantly between groups. Overall patient satisfaction (8 vs. 10, P = 0.034) and cosmetic satisfaction (6 vs. 9, P = 0.012) among VHR/STE were greater than VHR alone. CONCLUSION: Soft tissue resection during VHR results in greater patient satisfaction without increased costs.